\( \frac{7(x-3)}{x-4}+\frac{5}{x}=\frac{-5}{x(x-4)} \) Solve the following equation by factoring. A. The solution set is \( \{ \). (Type an integer or a simplified fraction. Use a comma to separate answers as needed.) B. There is no solution.
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To solve the equation \( \frac{7(x-3)}{x-4}+\frac{5}{x}=\frac{-5}{x(x-4)} \), we first find a common denominator, which is \( x(x-4) \). Multiplying through by the common denominator eliminates the fractions: \[ 7(x-3)x + 5(x-4) = -5 \] Next, we distribute and combine like terms: \[ 7x^2 - 21x + 5x - 20 = -5 \] This simplifies to: \[ 7x^2 - 16x - 15 = -5 \] Bringing -5 over gives: \[ 7x^2 - 16x - 10 = 0 \] Now, we can either factor or use the quadratic formula. In this case, we can factor the quadratic: \[ (7x + 5)(x - 2) = 0 \] Setting each factor to zero gives: 1. \( 7x + 5 = 0 \rightarrow x = -\frac{5}{7} \) 2. \( x - 2 = 0 \rightarrow x = 2 \) However, we must check for extraneous solutions by substituting back into the original equation. \( x = -\frac{5}{7} \) does not create any undefined expressions, whereas \( x = 2 \) also checks out without undefined expressions. Hence, the solution set is: A. The solution set is \( \{-\frac{5}{7}, 2\} \).